"Were They Ever Really Happy the Way That I Remember?": Exploring Sources of Uncertainty for Adult Children of Divorce. Issue 3 (3rd April 2017) - Abetz, Jenna; Wang, Tiffany R.
ABSTRACT: This study relies on interviews of adult children of divorce (ACOD) and the lens of uncertainty management theory to understand how ACOD construct and negotiate the uncertainty they face. Through our inductive analysis, we identified 4 major sources of uncertainty faced by ACOD: length of parental unhappiness, taking on new roles, navigating holidays and family events, and being caught in the middle. Exploring how this uncertainty is talked about and managed offers a theoretically and practically insightful glimpse into the meaning and sense-making processes as these individuals cope with one of the most prevalent and challenging events faced by families.